Epidemiological Characteristics and Clinical Manifestations of Hepatitis E in a Tertiary Hospital in China: A Retrospective Study - Fang, Li; Zhang, Junli; Chen, Huiying; Lv, Fangfang; Yu, Yunsong; Du, Xiaoxing (Frontiers in Microbiology, 2022)
Background: Hepatitis E virus (HEV) infection is the most common cause of acute viral hepatitis worldwide and one of the main causes of death in the last decade, causing chronic hepatitis and liver failure in some populations. The aging population and obesity are two major factors threatening human health. Therefore, we want to understand the relationship between these two groups and HEV infection. Objectives: The study aimed to analyze the epidemiological, clinical, and laboratory features of HEV infection, evaluate probable high-risk factors for disease progression, and the current diagnostic strategies of hepatitis E infection. Study design: Patients diagnosed with acute hepatitis E with symptoms and liver dysfunction were enrolled. For statistical analysis, clinical features and laboratory findings were collected between the elderly and non-elderly and HEV+ fatty liver disease (FLD) groups. Statistical analysis was performed using Excel and the platform VassarStats, and statistical significance was taken as P<0.05. Results: Jaundice and the bilirubin peak were significantly deeper, the duration of hospitalization was significantly longer, the proportion of ascites and liver failure was significantly higher in the elderly group. The aging population is one of the risk factors of severe hepatitis E. Hepatitis E becomes more serious in the HEV+FLD group, although the results did not reach statistical significance. Conclusions: The aging and FLD were suggested to aggravate HEV infection. However, the diagnosis of HEV infection remains a challenge. A prospective study with sufficient sample size is needed to confirm this conclusion.